2021
DOI: 10.1101/2021.03.09.434641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A recombinant ‘ACE2 Triple Decoy’ that traps and neutralizes SARS-CoV-2 shows enhanced affinity for highly transmissible SARS-CoV-2 variants

Abstract: The highly-transmissible SARS-CoV-2 variants now replacing the first wave strain pose an increased threat to human health by their ability, in some instances, to escape existing humoral protection conferred by previous infection, neutralizing antibodies, and possibly vaccination. Thus, other therapeutic options are necessary. One such therapeutic option that leverages SARS-CoV-2 initiation of infection by binding of its spike receptor binding domain (S RBD) to surface-expressed host cell angiotensin-converting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
4
2
0
Order By: Relevance
“…Our described effects on ACE2 binding and antibody evasion imparted by VoC/VoI RBD mutations are in agreement with recent reports (Chen et al, 2021;Collier et al, 2021;Dejnirattisai et al, 2021;Laffeber et al, 2021;Liu et al, 2021;Wang et al, 2021aWang et al, , 2021bWibmer et al, 2021;Yuan et al, 2021), with the exception of the enhanced ACE2 affinity conferred by E484K. Several studies have reported conflicting data surrounding the effect of E484K on ACE2 binding, where both decreased (Upadhyay et al, 2021;Wang et al, 2021c;Yuan et al, 2021) and increased (Laffeber et al, 2021;Tanaka et al, 2021) affinities are observed. A variety of biophysical techniques, spike protein domains, and ACE2 constructs were used across these studies, which could account for the contrasting results.…”
Section: Discussionsupporting
confidence: 91%
“…Our described effects on ACE2 binding and antibody evasion imparted by VoC/VoI RBD mutations are in agreement with recent reports (Chen et al, 2021;Collier et al, 2021;Dejnirattisai et al, 2021;Laffeber et al, 2021;Liu et al, 2021;Wang et al, 2021aWang et al, , 2021bWibmer et al, 2021;Yuan et al, 2021), with the exception of the enhanced ACE2 affinity conferred by E484K. Several studies have reported conflicting data surrounding the effect of E484K on ACE2 binding, where both decreased (Upadhyay et al, 2021;Wang et al, 2021c;Yuan et al, 2021) and increased (Laffeber et al, 2021;Tanaka et al, 2021) affinities are observed. A variety of biophysical techniques, spike protein domains, and ACE2 constructs were used across these studies, which could account for the contrasting results.…”
Section: Discussionsupporting
confidence: 91%
“…We also measured the efficiency of exogenously added soluble ACE2-mFc proteins to neutralize unmutated and N501Y pseudoviruses via preincubation prior to cell infection (S5B Fig) . The comparison of neutralization profiles shows that the IC 50 for neutralization of the N501Y mutant is lower, suggesting that full-length spikes bearing the N501Y mutation bind ACE2-mFc to a higher extent. Taken together with recent reports [22][23][24][25][26][27][28], these 3 results are consistent with the hypothesis that the greater infectivity of the N501Y mutant stems from improved binding to ACE2.…”
Section: The N501y Mutation Confers Increased Ace2 Binding Affinitysupporting
confidence: 91%
“…Our studies with the N501Y mutant are consistent with the expectation that the rapid spread of the UK variant of SARS-CoV-2 is likely due to the virus being more infectious. While there can be multiple origins for the increased infectivity, our biochemical studies suggest that the N501Y mutation results in increased ACE2 binding efficiency, a finding that has been reproduced by several recent studies [22][23][24][25][26][27][28]. Our structural studies establish the molecular basis underpinning the observed increase in ACE2 binding efficiency conferred by the N501Y mutation.…”
Section: Plos Biologysupporting
confidence: 82%
See 1 more Smart Citation
“…Tanaka et al performed a live virus neutralization assay in which they also reach 100% neutralization by using low concentration of ACE2-Ig, as opposed to our results. The reason behind the discrepancy might be in the method itself as they do not specify how the neutralization percentages were calculated and how the assay was performed [45]. Furthermore, we show that treatment with RBD-Ig using SARS-CoV-2 K18-hACE2 infected mice led to decrease in disease severity as assessed by reduced body weight, lower virus titers in the lungs, and higher survival percentage.…”
Section: Plos Pathogensmentioning
confidence: 86%